Decorated bullock carts - Mumbai Archive Project Team (Jio Institute, 2024)
The bullocks (and horses) are specially adorned with garlands, floral tassels hanging from their necks, and peacock feathers attached to their horns. Embroidered body covers are placed on their backs.